2017
DOI: 10.22159/ajpcr.2017.v10i11.17662
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Potential of Different Solvent Extracts of Some Medicinal Plants of Semi-Arid Region

Abstract: Objective: Infections caused by microorganisms that have become resistant to commonly used antibiotics have become a major nuisance globally. The problem of microbial resistance is increasing rapidly, and therefore there is an urgent need to develop novel antimicrobial agents from a natural source. The aim of the present study was to evaluate the antimicrobial activity of different solvent extracts of aerial part of Alysicarpus procumbens, Fimbristylis dichotoma, Saccharum spontaneum, Suaeda nigra, and Typha a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The antifungal activity of C. longirostrata is attributed to phenolic compounds, alkaloids, essential oils and glycosides [ 108 ]. Suaeda nigra shows inhibitory effects on gram-positive strains (Bacillus cereus ATCC11778, B. subtilis ATCC6633, Staphylococcus aureus ATCC29737 and Corynebacterium rubrum ATCC14898) and gram-negative bacteria (Escherichia coli NCIM2931, Pseudomonas aeruginosa ATCC9027, Salmonella typhimurium ATCC23564 and Klebsiella pneumonia NCIM2719) and has antifungal effects against Candida albicans ATCC209l, Cryptococcus neoformans ATCC34664, Candida glabrata NCIM3448 and Candida apicola NCIM3367 [ 109 ]. The dichloromethane extract of Porophyllum ruderale has antiparasitic activity against both promastigote and axenic amastigote forms of Leishmania amazonensis (leishmaniasis), with is the causal agent of a disease transmitted by mosquitoes [ 110 ].…”
Section: Antibacterial and Antifungal Activity Of Quelite Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antifungal activity of C. longirostrata is attributed to phenolic compounds, alkaloids, essential oils and glycosides [ 108 ]. Suaeda nigra shows inhibitory effects on gram-positive strains (Bacillus cereus ATCC11778, B. subtilis ATCC6633, Staphylococcus aureus ATCC29737 and Corynebacterium rubrum ATCC14898) and gram-negative bacteria (Escherichia coli NCIM2931, Pseudomonas aeruginosa ATCC9027, Salmonella typhimurium ATCC23564 and Klebsiella pneumonia NCIM2719) and has antifungal effects against Candida albicans ATCC209l, Cryptococcus neoformans ATCC34664, Candida glabrata NCIM3448 and Candida apicola NCIM3367 [ 109 ]. The dichloromethane extract of Porophyllum ruderale has antiparasitic activity against both promastigote and axenic amastigote forms of Leishmania amazonensis (leishmaniasis), with is the causal agent of a disease transmitted by mosquitoes [ 110 ].…”
Section: Antibacterial and Antifungal Activity Of Quelite Extractsmentioning
confidence: 99%
“…cyclopium, Botrytis cinerea, Colletotrichum capsici, Fusarium oxysporum, F. solani, Phytophthora capsici, Rhizoctonia solani and Sclerotinia sclerotiorum, fungi that causes diseases in crop plants. Additionally, C. nocturnum has antibacterial activity against Enterobacter cloacae (human isolate), Escherichia coli, Klebsiella pneumonia, Proteus vulgaris, Pseudomonas aeruginosa, Salmonella paratyphi A, S. paratyphi B, S. typhimurium, Shigella flexneri, Bacillus cereus (clinical isolate), Listeria monocytogenes, Micrococcus flavus and Staphylococcus aureus; these effects are attributed to different compounds, such as carbohydrates and/or glycosides, tannins, condensed tannins, hydrolysable tannins, alkaloids and/or nitrogenous bases, flavonoids, sterols and/or triterpenes, saponins and coumarins [ 109 ].…”
Section: Antibacterial and Antifungal Activity Of Quelite Extractsmentioning
confidence: 99%
“…For instance, polar extracts of C. ciliaris revealed significant antibacterial and antifungal activities against Proteus merabilis (MIC 0.234 mg/mL), Klebsiella pnemoniae (MIC 1.21 mg/mL) and Agerobacterium tumefaciens (MIC 4.24 mg/mL) [ 162 ]. Padalia and co-workers [ 163 ], through disk diffusion assay, evaluated different extracts of S. spontaneum ’s aerial parts and concluded that the petroleum ether, ethyl acetate, acetone, and methanol extracts were active against gram-positive bacteria (inhibition zones of 10.0, 11.0, 12.5 and 10.0 mm, respectively) [ 163 ]. Some of the compounds found in C. ciliaris and S. spontaneum are well known for their antimicrobial activity; however, its non-polar nature [ 164 ] prevent their presence in polar extracts.…”
Section: Biological Activities Of Halophytic Grassesmentioning
confidence: 99%
“…It can also be found in uplands with soil that retains water well. F. dichotoma has a moderate antibacterial activity against microorganisms, with a zone of inhibition of less than 50% for gram-positive, gram-negative, and fungi [18]. Therefore, the present study was aimed to investigate antioxidant, and antifungal potentials of methanol extracts of F. miliacea and F. dichotoma as well as analyse phytochemical content of the plant.…”
Section: Introductionmentioning
confidence: 99%